Five have plenty of fun - Blyton, Enid (Hodder Children's London, 2001)
George is not pleased when Berta, a spoilt American girl, turns up at Kirrin Cottage in the middle of the night - dressed in disguise! But George hasn't got time to be jealous. Berta is in hiding from kidnappers, and she needs help